Correlation between percutaneous biopsy and final histopathology for retroperitoneal sarcoma: a single‐centre study. Issue 4 (16th February 2020) - Young, Rebekah; Snow, Hayden; Hendry, Shona; Mitchell, Catherine; Slavin, John; Schlicht, Stephen; Na, Lumine; Hofman, Michael S.; Gyorki, David E.
Abstract: Background: Retroperitoneal sarcomas are rare soft tissue tumours accounting for 10–15% of soft tissue sarcomas. Patient prognosis and treatment recommendations (including extent of surgery and neoadjuvant strategies) are determined by the pre‐operative histopathological subtype and grade obtained from biopsy and thus it is important to understand the accuracy of biopsy in retroperitoneal masses. Methods: This study presents a case series of primary retroperitoneal sarcomas managed at Peter MacCallum Cancer Centre (PMCC) between 2008 and 2019. Statistical analyses were performed to determine correlation between histopathology from percutaneous biopsy and surgical excision. Results: A total of 117 patients who underwent percutaneous core biopsy and surgical excision of retroperitoneal sarcoma were included. Diagnostic accuracy varied with histopathological diagnosis, but overall precise concordance between biopsy and final histopathology was seen in 61% (κ = 0.57). Biopsy was most sensitive for identifying well‐differentiated liposarcoma (WDLPS) (sensitivity 85%, 95% CI 0.06–0.96) and leiomyosarcoma (sensitivity 81%, 95% CI 0.54–0.96) and was least sensitive for identifying de‐differentiated liposarcoma (DDLPS) (sensitivity 40%, 95% CI 0.25–0.56). Overall agreement between biopsy and final histopathology increased with use of PET/CT scan pre‐biopsy and with use of fluorescence in situ hybridisation testing on biopsy, however, neither test improved recognition of de‐differentiated components within WD/DDLPS on core biopsy. Conclusions: Pre‐operative biopsy is important for clinical decision making in the treatment of retroperitoneal sarcoma. A significant portion of patients with a WDLPS will have a de‐differentiated component identified at the time of resection that was not identified on initial biopsy. Abstract : Retroperitoneal sarcoma is a rare and heterogeneous condition which can be difficult to diagnose accurately. This study analysed the accuracy of percutaneous biopsy for determining final histopathology in a cohort of 117 patients with retroperitoneal sarcoma managed at an Australian specialist sarcoma centre.